IMPLEMENTASI PENERAPAN (P5) TEMA KEWIRAUSAHAAN PEMANFAATAN LIMBAH PERTANIAN DAN PETERNAKAN PADA SISWA KELAS VIII DI SMP NEGERI 1 WULUHAN - Iwana Laela Agustias; Johanes Agung Indratmoko; Peni Catur Renaningtyas (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to examine the tendency of students’ mutual cooperation behavior through the implementation of the Pancasila Student Profile Strengthening Project (P5). The background of the research is the importance of character education, especially the value of gotong royong (mutual cooperation), which is fundamental in Indonesian society. This study used a descriptive qualitative method with data collected through observation, interviews, and documentation. The findings show a significant increase in students’ mutual cooperation behavior during and after the P5 implementation. Indicators such as helping each other, shared responsibility, and group participation shifted from low or moderate levels to high levels. These results are aligned with contextual learning theory which emphasizes learning through meaningful experiences. The findings support previous studies that demonstrate the role of project-based learning in developing collaborative values. In conclusion, the P5 program is effective in fostering the value of mutual cooperation among students through experiential and collaborative learning processes.